Interaction of accommodative and subjective diagnostic criteria of accommodation disorders - M. V. Makhova; V. V. Strakhov (Российский офтальмологический журнал)
Purpose: to study the relationship of accommodative (objective) and subjective criteria of different types of accommodation disorders.Material and methods. 62 patients (124 eyes) with myopic refraction, aged 10 to 18, were divided into 6 groups according to accommodation disorders types. All patients were tested objectively on a Speedy-i accommodograph, which determined the coefficient of accommodation response (CAR) and the coefficient of microfluctuations (CMF) and underwent MEM retinoscopy to determine the accommodation response. In addition, subjective methods were used to determine the amplitude of accommodation (by proximetry) and accommodation flexibility (by ±2 D flipper). Results. A rather close correlation was revealed between the accommodative and subjective evaluation criteria of ciliary muscle performance. Therefore, both the CAR and proximetry data may be used to determine accommodation amplitude. The power of accommodation response may be determined by CAR and MEM retinoscopy, while the accommodation state may be tested by CMF or accommodation flexibility.Conclusion. A statistically significant correlation between accommodative coefficients and the results of subjective tests enable the practitioners of outpatient care to use the available subjective methods of accommodation disorder diagnosis and, accordingly, determine the best suited optical correction and choose adequate methods of treatment of accommodation disorders.